A South African perspective: audiologists' and otologists' orientation to, and use of evidence-based practice with reference to benign paroxysmal positional vertigo - Naidoo, Tanaya Ellen Ravi (Division of Communication Sciences and Disorders, 2022)
Evidence-based practice, whose roots emanate from the mid-1960s, aims to provide fair, high-quality, and soundly researched health care with patients' best interests as a priority. Clinical practice guidelines are evidence-based and designed to assist clinicians with sound decision making. Despite the importance of evidence-based practice and the efforts invested into its development and dissemination, its uptake and implementation are poor. The disconnect between evidence-based practice and its translation into clinical practice was previously reported in low-to-middle income countries. This study investigated South African audiologists' and otorhinolaryngologists' (ear, nose and throat specialists') self-reported orientation to evidence-based practice. Second, adherence to evidence-based clinical practice guidelines was assessed with reference to the diagnosis and management of benign paroxysmal positional vertigo, a common vestibular condition for which a firm evidence base supporting treatment exists. A two-part quantitative approach was adopted. Part one surveyed South African audiologists and otorhinolaryngologists with the Evidence-Based Practice Profile Questionnaire and an additional researcher-developed questionnaire pertaining to the diagnosis and management of benign paroxysmal positional vertigo. A total of 130 survey responses were included in this study. Independent sample t-tests, one-way ANOVAs and Fisher's Exact tests were used to analyse the survey data. Part two used a retrospective record review at a tertiary academic hospital in the Western Cape of South Africa. Medical folders of patients diagnosed with benign paroxysmal positional vertigo, between 2010 – 2018 (n = 80), were analysed. The diagnosis and management strategies were recorded and compared against a gold standard evidence based guideline for congruence. Descriptive statistics were used to analyse and understand the data. Survey scores showed a positive association between increased years of experience and healthcare professionals' knowledge (p = .008) and confidence (p = .003) in evidence-based practice. Otorhinolaryngologists might be more knowledgeable than audiologists in evidence-based practice due to their increased training and exposure to evidence-based practice in their specialising years. Findings from the retrospective record review suggested adherence to the clinical practice guidelines in the diagnosis and management of posterior semi circular canal benign paroxysmal positional vertigo. The study outcomes propose that evidence-based clinical practice guidelines developed in the Global North may not be appropriate for the different health contexts that exist in low-to-middle income South Africa (e.g., rural settings). However, the benign paroxysmal positional vertigo clinical practice guidelines were adhered to at a tertiary, academic hospital in Cape Town. The results also support the notion that increased exposure to evidence-based practice reinforces its approach. Outcomes from this study raise implications for the development and dissemination of context-appropriate, evidence-based clinical practice guidelines.